Poor nutritional status of fifteen-year-old or younger adolescent mothers enhances the risk of small-for-gestational-age newborns - Alves, Maria Francisca; Corleta, Helena von Eye; Capp, Edison; Lubianca, Jaqueline Neves (Clinical and Biomedical Research, 2023)
Introduction: To analyze the factors (socio-demographic, clinical, prenatal care, delivery, postpartum data and anthropometric measures) associated with the birth of small for gestational age newborns. Methods: A cross-sectional study was performed with 15 years old or younger postpartum adolescents divided into small-for gestational-age newborn (SGA) and non-small-for-gestational age newborn groups (NSGA). Socio-demographic, clinical, prenatal care, delivery, postpartum data and anthropometric measures (triceps skinfold (TS), and mid-arm circumference, (MAC)) were collected. Results: 8,153 women gave birth at the obstetric ward and 364 (4.46%) ≤ 15 years old adolescents were enrolled in the study. The proportion of SGA newborns was 34.61%. The SGA group attended fewer prenatal visits (p = 0.037), had a higher prevalence of nutritional status classified as “very low weight” (p < 0.001) and vaginal delivery (p = 0.023), compared to the NSGA group. The nutritional status and vaginal delivery remained significant even after adjustment for confounders. The prevalence risk for SGA birth was 30% higher in the group of mothers with nutritional status classified as “very low weight” (odds ratio 1.30, 95% confidence interval 1.13 to 1.50) (p < 0.001). Conclusions: 15.4% of adolescents ≤ 15 years of age had an arm circumference compatible with the “very low weight” condition, demonstrating the high prevalence of poor maternal nutritional status in this group. The birth of SGA among adolescents ≤ 15 years of age is independently associated with maternal nutritional status classified as “very low weight” by the mid-arm circumference measures (MAC).